On Reanalyzing the Harris-Todaro Model: Policy Rankings in the Case of Sector-Specific Sticky Wages - Bhagwati, Jagdish N.; Srinivasan, T. N. (American Economic Review, 1974)
In a brilliant and pioneering paper, John Harris and Michael Todaro introduced a model with two sectors, manufacturing (urban) and agriculture (rural), a (sticky) minimum wage in manufacturing and consequent unemployment. They also introduced a labor allocation mechanism under which, instead of the usual equalization of actual wages, the actual rural wage was equated with the expected urban wage; the latter was defined as the (sticky) minimum wage weighted by the rate of employment, so that, unlike in the standard rigid-wage models of trade theory, the unemployment resulting from the minimum wage is to be construed as specific to the urban sector. In the context of this model, Harris and Todaro analyze two policies: a wage subsidy policy in the manufacturing sector and a labor-mobility restriction policy. They argue that the former, as well as the latter, can be used to improve welfare, defined as a function of available goods in the usual way; but that, to attain the optimal first best solution, both policies are necessary.